The spring-like effect of microRNA-31 in balancing inflammatory and regenerative responses in colitis - Qu, Jing; Shao, Chunlei; Ying, Yongfa; Wu, Yuning; Liu, Wen; Tian, Yuhua; Yin, Zhiyong; Li, Xiang; Yu, Zhengquan; Shuai, Jianwei (Frontiers in Microbiology, 2022)
Inflammatory bowel diseases (IBDs) are chronic inflammatory disorders caused by the disruption of immune tolerance to the gut microbiota. MicroRNA-31 (MIR31) has been proven to be up-regulated in intestinal tissues from patients with IBDs and colitis-associated neoplasias. While the functional role of MIR31 in colitis and related diseases remain elusive. Combining mathematical modeling and experimental analysis, we systematically explored the regulatory mechanism of MIR31 in inflammatory and epithelial regeneration responses in colitis. Level of MIR31 presents an “adaptation” behavior in dextran sulfate sodium (DSS)-induced colitis, and the similar behavior is also observed for the key cytokines of p65 and STAT3. Simulation analysis predicts MIR31 suppresses the activation of p65 and STAT3 but accelerates the recovery of epithelia in colitis, which are validated by our experimental observations. Further analysis reveals that the number of proliferative epithelial cells, which characterizes the inflammatory process and the recovery of epithelia in colitis, is mainly determined by the inhibition of MIR31 on IL17RA. MIR31 promotes epithelial regeneration in low levels of DSS-induced colitis but inhibits inflammation with high DSS levels, which is dominated by the competition for MIR31 to either inhibit inflammation or promote epithelial regeneration by binding to different targets. The binding probability determines the functional transformation of MIR31, but the functional strength is determined by MIR31 levels. Thus, the role of MIR31 in the inflammatory response can be described as the “spring-like effect”, where DSS, MIR31 action strength, and proliferative epithelial cell number are regarded as external force, intrinsic spring force, and spring length, respectively. Overall, our study uncovers the vital roles of MIR31 in balancing inflammation and the recovery of epithelia in colitis, providing potential clues for the development of therapeutic targets in drug design.